New Insights into the Building Design and Construction Phases of the Constantinian Bishop’s Church at Ostia: Results from the Initial Excavation, 2023 - Feist, Sabine; Heinzelmann, Michael; Zimmermann, Norbert; Borgia, Emanuela; Boes , Hannah; Schröder , Arne; Elefante, Mara; Troiani, Angelita; Russo, Francesca (Römische Mitteilungen, 2024)
The initial excavation that took place under the auspices of the new DFG project, ‘The Constantinian Bishop’s Church at Ostia: Structure – Development – Context’ (Die konstantinische Bischofskirche von Ostia: Struktur – Entwicklung – Kontext) concentrated on the eastern part of the building, including the apse and presbytery. This excavation has already provided new and foundational insights that not only bring markedly greater precision to our knowledge of the Ostian cathedral, but also generally shed new light on Constantinian basilicas in the greater Roman region and provide evidence of previously unknown building phases and liturgical fixtures. For example, the foundations of the recessed apse revealed projecting walls on which columns probably stood. These columns would have framed the apse and also borne the weight of the apsidal arch. As such, this is a variant of apse architecture otherwise undocumented in Rome, now evident at the very beginning of Constantine’s church construction programme. Secondarily, a solea was built into the nave that likewise displays an unusual form. Finally, a chord of the apse was added most likely during the late 6th or early 7th century, probably when the apse was renovated after it was partially destroyed. Such a renovation project attests to a surprising degree of economic potential held by the Ostian bishopric, even at this relatively late stage of the city’s history. These results are presented below, according to the current state of research.